VD_FINDINFO Pron / 2014 / 29 vom 25. März 2014 - VD Tribunal cantonal (2014)
ASSISTANCE JUDICIAIRE, TRANSACTION JUDICIAIRE | 109 al. 1 CPC (CH), 117 let. a CPC (CH), 119 CPC (CH), 122 CPC (CH), 241 CPC (CH)